Pendampingan untuk pengembangan Kompor TLUD dalam Pemanfaatan Ampas Sagu sebagai Biopelet dalam Mewujudkan Transisi Energi di Desa Maini Kabupaten Kepualuan Meranti - Hafidawati, Hafidawati; Yenie, Elvi; Zahrina, Ida; Setiaries, Vonny; Kurniawan, Iwan; Musfar, Tengku Firly (Unri Conference Series: Community Engagement, 2024)
The Assisted Village Service Program was carried out in Maini Darul Aman Village, Tebing Tinggi Barat District, Meranti Islands Regency. This activity aims to assist the community in overcoming the problem of sago pulp waste that has not been optimally utilized. During this time, sago pulp waste is disposed of in a shelter or along the river flow around the sago processing site, which has the potential to pollute the environment. As a solution, this program offers the production of biopellets from sago pulp, which can be used as an alternative to conventional fuels such as firewood and kerosene, and has the potential to become a business opportunity that can improve the family economy. This activity was carried out through several stages, including: socialization to the community about the importance of sago waste management, its impact, and the solutions offered; assistance in processing sago pulp into biomass biopellets; and assistance in using TLUD stoves fueled by sago pulp pellets. The final stage is coaching in marketing management as part of the future development of this program. The Bina Desa program is also integrated with UNRI students' Community Service Program (KKN) activities in 2024, which runs from July to the end of August 2024. Through this program, it is expected that the community can continue to develop the use of biopellets as fuel, both for household needs and industrial scale, such as use in boilers. In addition to protecting the environment, it is hoped that this program can also be a source of income that can improve the welfare of the community.